DISTINGSI PENGELOLAAN KONFLIK PAPUA YANG TIDAK PERNAH SELESAI - Jalaluddin Hasibuan (ASKETIK: JURNAL AGAMA DAN PERUBAHAN SOSIAL, 2022)
The conflict which occurred in Papua began in 1961 until the era of reform, continuously the government made efforts to overcome the conflict. During the New Order the government took a repressive approach by making Papua a Military Operations Area (Daerah Operasi Milite or DOM). During the reformation, the government sought to use a persuasive humanist approach. However, very complex problems caused the intensity of conflict in Papua to increase, the more widespread and more open. The research aimed to summarize and evaluate the management process and conflict resolution carried out by the government against Papua. This research used a qualitative approach with this type of library research. The results showed that conflict in Papua could be categorized into two models, social conflict and political conflict. In the era of reform conflict resolution initiatives were still in the state of social conflict, although the results had not been maximal. While political conflict had never been done by mediation.